Implementasi Sadar Wisata di Bukit Holbung – Desa Wisata Hariara Pohan, Kabuapten Samosir, Provinsi Sumatera Utara - Deafani Clara Sinaga (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2023)
This study discusses how to implementation tourism awareness in the Sapta Pesona approach at Holbung Hill (Bukit Holbung) Hariarapohan Tourism Village, Samsosir Regency, North Sumatera Province. This study uses qualitative research methods, which is used to research in scientific conditions (experiments) where researchers as research instruments, data collection techniques and qualitative analysis put more emphasis on meaning. In this study the research instrument was the researcher himself or human instrument, and the key informants were the Chairperson of the Pokdarwis, the Head of Indigenous Peoples / Homestay Manager, the Tourism Consultant, the Community at Bukit Holbung to be precise in Hariarapohan Village. The data collection technique is through interviews and observations, then the data obtained is analyzed descriptively by describing or describing the data that has been collected and general conclusions are drawn. The result of the research that the application of Tourism Awareness in Holbung Hill, Hariarapohan Village has been implemented properly, just not optimal because some people still don't care about tourism activities at Holbung Hill, because of the mindset of the people who want immediate results, and they don't understand that tourism requires a long process to see the results of these tourism activities. Keywords: Tourism Awarness, Tourism Village, Seven Charms (Sapta Pesona), Community.